2019
DOI: 10.1088/1361-6552/ab299f
|View full text |Cite
|
Sign up to set email alerts
|

Image processing for quantitative measurement of e/m in the undergraduate laboratory

Abstract: In conventional e/m experiments performed in undergraduate laboratories, generally a simple mechanical ruler is used to measure the radius of the circular trajectory of the electrons. But, the measurement error in this technique is mostly big and varies from one student to another. As an alternative to a mechanical ruler, we proposed a more accurate and a more precise technique for measuring the radius. This technique is based on image processing and it is well known that the image processing is one of the mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
2
0
3
Order By: Relevance
“…Çalışmaların çoğunluğunda her ne kadar hedeflenen öğretim seviyesi belirtilmese de öne sürülen deneyler için üniversite seviyesinde bilgi ve beceri gerektiği görülmektedir (Gelir, Kocaman & Pekacar, 2019;Hughes, Evason, Nadarajah & Leisemann, 2019). Bunun yanında manyetik alan kavramını içeren ve daha düşük öğrenim düzeylerine hitap eden çalışmalar da dergide yer almaktadır (Bergmann, Dürr & Rockstuhl,2019;Boyle, 2019).…”
Section: Sonuç Ve Tartışmaunclassified
See 1 more Smart Citation
“…Çalışmaların çoğunluğunda her ne kadar hedeflenen öğretim seviyesi belirtilmese de öne sürülen deneyler için üniversite seviyesinde bilgi ve beceri gerektiği görülmektedir (Gelir, Kocaman & Pekacar, 2019;Hughes, Evason, Nadarajah & Leisemann, 2019). Bunun yanında manyetik alan kavramını içeren ve daha düşük öğrenim düzeylerine hitap eden çalışmalar da dergide yer almaktadır (Bergmann, Dürr & Rockstuhl,2019;Boyle, 2019).…”
Section: Sonuç Ve Tartışmaunclassified
“…Bu durumda öğretmenlerin pedagojik alan bilgilerini uygun şekilde kullanabilmeleri devreye girmektedir. (Saranin, Keldyshev & Ivanov, 2019), akıllı telefon uygulamaları (Çoban & Erol, 2019;Pili, 2019;Soares & Reis, 2019), bilgisayar yazılımları (Gelir, Kocaman & Pekacar, 2019), sensörler (Oliveira, 2019) örnek olarak gösterilebilir. Bu tür uygulamaların manyetik alan kavramının diğer konu ya da disiplinler ile ilişkilendirilmesini kolaylaştıracağı; bu kavramın öğretimini daha etkili bir hale getireceği düşünülmektedir.…”
Section: Sonuç Ve Tartışmaunclassified
“…A recent paper [16] in this journal showed that the image processing software ImageJ can be used to analyse particle trajectories in Bainbridge tubes. Tracker offers several advantages over ImageJ.…”
Section: Determining the Radius Of Curvature With Trackermentioning
confidence: 99%
“…The entire experimental apparatus is quite accessible and only a simple laser and an ordinary smartphone are required. The estimation of the fractal dimension is performed using the free software ImageJ, which can be used for didactic proposals [16]. Moreover, the experiment, which allows the discussion of several fundamental physics concepts, is easy to replicate and no more than two lessons are necessary to perform the full activity, including measurements, data treatment and discussion.…”
Section: Introductionmentioning
confidence: 99%